Global mapping of freshwater contamination by pesticides and implications for agriculture and water resource protection - Yabi Huang; Zijian Li (iScience)
Summary: Pesticide residues in freshwater threaten water sustainability, but the global discrepancies in freshwater pesticide contamination remain uncertain. This study collected pesticide concentration data from various countries around the world and adopted a flexible scoring approach to assess contamination within surface freshwater and groundwater. Results revealed significant disparities in contamination among countries. Africa was identified as a priority for freshwater pesticide control as most countries there showed relatively high scores in both surface freshwater and groundwater. Notably, robust pesticide regulations were associated with reduced surface freshwater pollution, whereas pesticide usage intensity showed no clear effect. Additionally, pesticide residues in freshwater pose challenges to drinking water safety, with over half of the water samples in many African and Asian countries exceeding aldrin and dieldrin limits. These findings provide insight into the pattern of global pesticide freshwater contamination, urging efforts on comprehensive water monitoring networks and joint pesticide management within freshwater.